y = 4x – 2
A. (0, 3)
B. (1, 2)
C. (2, 1)
D. (0, −2)
Answer:
B. (1,2)
Step-by-step explanation:
y = –x + 3.......(1)
y = 4x – 2.......(2)
Putting (1) into (2)
-x + 3 = 4x - 2
4x + x = 3 + 2
5x = 5
x = 5/5
x = 1
And putting x = 1 in (1)
y = -x + 3
y = -1 + 3
y = 2
Answer:
B. (1, 2)
Step-by-step explanation:
YEP!! YOUR ANSWER IS B (1, 2)
Putting (1) into (2)
-x + 3 = 4x - 24x + x = 3 + 2
5x = 5
x = 5/5
x = 1
And putting x = 1 in (1)
y = -x + 3
y = -1 + 3
y = 2
A.
15.8 ft
B.
14.1 ft
C.
16.0 ft
D.
20.0 ft